The Expertise of Entrepreneur that must have on Increasing the Business Profit - Hardiyanti, Siti Epa; Nemat, Masihullah (Management Science Research Journal, 2022)
This research was conducted to see the effect of qualification an entrepreneur (education level, financial literacy, and gender) on increasing business profits. The population on this study were MSMEs in the Kalongan Village area, totaling 116 MSMEs and the sampling technique used was an observation. The research method using multiple regression analysis to explore the effect of education, gender, and financial literacy on business profits. The results of the analysis found that (1) the level of education has a positive and significant effect on business profits; (2) gender has a positive and significant effect on business profits; (3) Financial literacy has a positive and significant effect on business profits. The implication of the research is Business profits can be determined by several skill qualifications that must be owned by an entrepreneur, including the level of education, gender, and financial literacy knowledge.